Operational Risk Management in an Unstable Global Supply Chain - Diatio Yulianto; Dwi Utami Puterisari (PT. Hafasy Dwi Nawasena, 2025)
Global supply chain instability driven by geopolitical volatility, climate-related disruptions, energy crises, and logistical bottlenecks has intensified operational risks across industries. This study aims to analyze key sources of operational risk and identify effective mitigation strategies using a Systematic Literature Review (SLR). The SLR process involved the identification, screening, eligibility assessment, and thematic analysis of 26 relevant peer-reviewed publications from the last decade. The findings reveal that operational risks originate from supplier fragility, geographic dependency, macroeconomic uncertainty, climate-related hazards, and technological vulnerabilities. Mitigation strategies identified include supplier diversification, inventory optimization, digital visibility systems, production regionalization, scenario modeling, and inter-organizational risk collaboration. The study also finds that an integrated risk management model such as incorporating digital early-warning systems, rapid response capabilities, long-term adaptive capacity, and strategic collaboration, offers the most effective approach to enhancing global supply chain resilience. It concludes that firms must strengthen technological integration and organizational capacity to respond adaptively to disruptions, while public-policy support is essential to reinforce logistics infrastructure and digitalization, particularly in developing economies.